Penerapan Terhadap Analisis Swot Pada Usaha First Hook Coffee - Benny Carlson (ConCEPt - Conference on Community Engagement Project, 2021)
Author start the internship program towards Small Micro Medium Enterprises (SMME) First Hook Coffee Shop’s business in August 12th 2018. SMME is located at Perum Nusa Jaya Blok F No 11, Sungai Panas. This SMME belongs to Mr. Hendry, needs strategic to deal with other SMME. Author wants to help owner of First Hook Coffee Shop to improve the selling strategy by building new strategy in order to compete with other competitors. During implementing this practical work, author gather information to do background analysis of First Hook Coffee Shop. After analysis, author adopted a strategy to enable Mr. Hendry's business to compete and run better than before. The problem with the implementation of this strategy is the lack of preparation to run the strategy, therefore more time is needed to implement the strategy formulated by the author. The strategy is the SWOT matrix. Author thought that this is the best strategy to deal with new competitors in the current situation. Small Micro Medium Enterprises First Hook Coffee Shop implemented SWOT Matrix that thought and made by author. Author provide social media for First Hook Coffee Shop to owner so that he can up-to date about every promotions through Instagram and Go-Food, so that all of the customer will know any promotion that being made by First Hook Coffee Shop.